Dual-Functional Photonic Metacoating Integrating Fluorescence Thermometry and High-Performance Space Radiative Cooling - Gong, Hao; Wang, Zhongyang; Zheng, Yan; Tong, Liping; Li, Hongchao; Zhao, Zhiyuan; Liu, Junjia; Liu, Gang; Zhou, Xiao; Fan, Tongxiang (Nano-Micro Letters, 2026)
Fluorescence thermometry offers a non-contact strategy for early detection of thermal instabilities on complex spacecraft surfaces, enabling reliable in-orbit temperature mapping. However, simultaneously achieving high-sensitivity fluorescence thermometry and efficient space radiative cooling remains challenging, as enhanced visible absorption improves thermometric response but increases solar heating. Here, we address this trade-off through a material-structure co-design strategy by developing an Eu-doped ZrO2 submicrosphere metacoating that integrates space radiative cooling with fluorescence-based temperature sensing. Guided by photonic-structure optimization using a constrained-gradient optimizer combined with grid-search mapping, the optimized metacoating, featuring a submicrosphere diameter of 0.756 µm and a volume fraction of 35%, achieves an ultralow solar absorptance (αs = 0.076) and a high thermal emittance (ε = 0.931). In parallel, bandgap-driven compositional optimization identifies an optimal Eu content of 8.48%, enabling outstanding thermometric performance. The metacoating delivers a net cooling power of 323.69 W m−2 and a 77 °C temperature reduction relative to an Al sheet, outperforming representative oxide-based inorganic coatings. It allows temperature sensing over 173–433 K with a maximum relative sensitivity of 0.797% K−1, surpassing fluorescent oxides with comparable absorption edges. Moreover, the metacoating maintains the lowest αs and reliable irradiation resistance under proton, electron, atomic oxygen and ultraviolet exposures, outperforming reported counterparts. Together with its scalable fabrication, this work establishes a dual-functional metacoating platform for intelligent spacecraft thermal management that combines efficient radiative cooling with high-sensitivity fluorescence thermometry. Highlights: 1 Dual-functional Eu-doped ZrO2 submicrosphere metacoating for space radiative cooling and fluorescence thermometry. 2 Photonic structure and materials co-design yield an ultralow solar absorptance (αs = 0.076) and high emittance (ε = 0.931) in a 100 μm thick metacoating. 3 The metacoating achieves a net cooling power of 323.69 W m−2 and enables 173–433 K non-contact thermometry (Sr,max = 0.797% K−1) with reliable irradiation resistance under space environments.